2017
DOI: 10.1002/slct.201700231
|View full text |Cite
|
Sign up to set email alerts
|

Direct Chiral Separation of Binaphthyl Derivatives Using Atroposelective Antibodies

Abstract: A simple procedure for chiral separation based on the difference in the molecular weights of the antigen-antibody complex and analyte is developed. We raise monoclonal antibodies (mAbs) highly specific for the R-or S-isomer of a binaphthyl derivative (BN) by immunizing mice with the corresponding BN enantiomer. Aqueous solutions of racemic BN are mixed with mAbs. The free BN is separated by ultrafiltration. The enantiomers of BN are obtained with a high e.e. using atroposelective antibodies.Chirality is crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Recently, Harada and coworkers employed monoclonal antibodies (mAbs) as protein scaffolds for ArMs catalyzing Friedel–Crafts reactions [ 66 ]. They previously developed atroposelective mAbs by immunological optimization of mAbs over binaphthyl (BN) derivatives [ 67 , 68 ]. These anti-BN mAbs could bind 1,1′-bi-isoquinoline (BIQ)-based metal catalysts and provide a chiral environment for the selective reaction.…”
Section: Recent Progress On the Various Reactions Catalyzed By Armmentioning
confidence: 99%
“…Recently, Harada and coworkers employed monoclonal antibodies (mAbs) as protein scaffolds for ArMs catalyzing Friedel–Crafts reactions [ 66 ]. They previously developed atroposelective mAbs by immunological optimization of mAbs over binaphthyl (BN) derivatives [ 67 , 68 ]. These anti-BN mAbs could bind 1,1′-bi-isoquinoline (BIQ)-based metal catalysts and provide a chiral environment for the selective reaction.…”
Section: Recent Progress On the Various Reactions Catalyzed By Armmentioning
confidence: 99%
“…Recently, we revealed that mAbs prepared by immunization with R -and S -4,4′-([1,1′-binaphthalene]-2,2′-diylbis(oxy))dibutanoic acid (BN ( R ) and BN ( S ) in Fig. 1a) or racemic BN precisely recognize the axial chirality of BN 43,44 . Hence, we defined the anti-BN mAbs as an atroposelective antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we defined the anti-BN mAbs as an atroposelective antibody. The chiral recognition ability has been applied to operationally simple and rapid chiral separation and chiral sensing systems 43,45 .
Figure 1Design strategy for artificial metalloenzymes based on atroposelective antibodies. Atroposelective antibodies generated against a structurally simple binaphthyl derivative (BN) ( a ) are used to accommodate various BIQ-based metal catalysts ( b ).
…”
Section: Introductionmentioning
confidence: 99%
“…The atroposelectivity of mAbs has been exploited in a column-free chiral separation with a one-step simple procedure. 29 We expect that optical isomers can be distinguished by the naked eye without any special instruments. 3034 Here we demonstrate that one of the mAbs elicited against the S-isomer of BN [BN (S)] can be used to differentiate BN (S) from BN (R).…”
mentioning
confidence: 99%